Inhibition of Cathepsin S Produces Neuroprotective Effects after Traumatic Brain Injury in Mice - Jianguo Xu; Handong Wang; Ke Ding; Xinyu Lu; Tao Li; Jiawei Wang; Chunxi Wang; Jian Wang (Mediators of Inflammation)
Cathepsin S (CatS) is a cysteine protease normally present in lysosomes. It has long been regarded as an enzyme that is primarily involved in general protein degradation. More recently, mounting evidence has shown that it is involved in Alzheimer disease, seizures, age-related inflammatory processes, and neuropathic pain. In this study, we investigated the time course of CatS protein and mRNA expression and the cellular distribution of CatS in a mouse model of traumatic brain injury (TBI). To clarify the roles of CatS in TBI, we injected the mice intraventricularly with LHVS, a nonbrain penetrant, irreversible CatS inhibitor, and examined the effect on inflammation and neurobehavioral function. We found that expression of CatS was increased as early as 1 h after TBI at both protein and mRNA levels. The increased expression was detected in microglia and neurons. Inhibition of CatS significantly reduced the level of TBI-induced inflammatory factors in brain tissue and alleviated brain edema. Additionally, administration of LHVS led to a decrease in neuronal degeneration and improved neurobehavioral function. These results imply that CatS is involved in the secondary injury after TBI and provide a new perspective for preventing secondary injury after TBI.